Surface energy and wettability of polymers light-cured by two different systems - Fatima Maria Namen; Eduardo Ferrandini; João Galan Junior (University of São Paulo, 2011)
OBJECTIVE: This study evaluated the surface energy and wettability of composite resins polymerized by different light-curing units to ascertain the good wetting of tooth surfaces to achieve adhesion. MATERIAL AND METHOD: Filtek Z350 (3M ESPE), Admira (VOCO) and Grandio (VOCO) resins were selected for the testing procedures. The resins were light cured using LED and Halogen devices. Contact angles were measured goniometrically (Ramé-Hart F100) using water and glycerol as test liquids. Surface energy values were calculated with a software program (DROPimage Standard) that uses the harmonic mean method applied to the acid-base theory. The data were analyzed statistically by ANOVA and Tukey's test with a significance of 0.05. RESULTS AND CONCLUSIONS: No statistically significant differences were found between the values of surface energy. The measured wettability differed statistically in most combinations as a function of the type of composite resin, type of light-curing unit, and the test liquid.